Perceived Loneliness and Severe Sleep Disorders in Adult Women during the Covid-19 Quarantine: A Cross-Sectional Study in Colombia (2021)
Background: Quarantine is a measure to control COVID-19 spread, resulting in an increased perception of loneliness. In turn, sleep disorders (SD) may be more frequently reported in uncertain circumstances. Objectives: To identify the association between loneliness and severe SD, in women quarantined due to the COVID-19 pandemic. Methods: A cross-sectional study carried out in women, between 40 and 79 years and living in Colombia. The women were invited through social network to complete 5 digital instruments: de Jong Gierveld Loneliness Scale, Menopause Rating Scale, Fear of COVID-19 Five-item Version, Coronavirus Anxiety Scale, and Francis Religion Scale. Bivariate analysis and adjusted logistic regression between loneliness and SD were performed. Results: 1133 women participated, half of them under 50 years old. 43.1% had emotional loneliness, 39.9% social loneliness and 43.3% general loneliness. SD were identified in 6 out of 10 women, those with mild SD presented an OR of 1.84, 1.85, and 1.64, for emotional, social and general loneliness, respectively. Loneliness was associated twice with moderate SD, and more than twice with severe SD. Very severe SD reached OR:5.81 for emotional loneliness, OR:4.38 social loneliness and OR:4.02 general loneliness. In the presence of religiosity, fear and anxiety due to COVID-19, statistical significance was retained for associations, except intense SD with general loneliness. Conclusions: SD were significantly associated with loneliness in our study population. It is important to assess sleep quality and perception of loneliness in middle-aged women, especially during periods of quarantine due to a pandemic to avoid health implications.